Accounting for Cloud Computing in the National Accounts - Baer, Andrew; Lee, Kwangwon; Tebrake, James (Washington, D.C. : International Monetary Fund, 2020)
Digitalization and the innovative use of digital technologies is changing the way we work, learn, communicate, buy and sell products. One emerging digital technology of growing importance is cloud computing. More and more businesses, governments and households are purchasing hardware and software services from a small number of large cloud computing providers. This change is having an impact on how macroeconomic data are compiled and how they are interpreted by users. Specifically, this is changing the information and communication technology (ICT) investment pattern from one where ICT investment was diversified across many industries to a more concentrated investment pattern. Additionally, this is having an impact on cross-border flows of commercial services since the cloud service provider does not need to be located in the same economic territory as the purchaser of cloud services. This paper will outline some of the methodological and compilation challenges facing statisticians and analysts, provide some tools that can be used to overcome these challenges and highlight some of the implications these changes are having on the way users of national accounts data look at investment and trade in commercial services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet